Can a mock medication-taking learning activity enable pharmacy students to experience the range of barriers and facilitators to medication adherence? An analysis informed by the Theoretical Domains Framework and COM-B model - E. Mantzourani; D.H. James; M.A. Akthar; S.L. Brown; R. Yemm; E.C. Lehnbom; J.R. Hanrahan; C.H. Seage (Elsevier, 2024)
Background: Pharmacy professionals are well-placed to provide medication adherence support to patients. The Capability, Opportunity, Motivation-Behaviour (COMB) and Theoretical Domains Framework (TDF) are two complementary models previously applied to medication-taking behaviour. Understanding the patient-specific barriers and facilitators to adherence using psychological frameworks from the early stages of pharmacy education enables the design and delivery of effective interventions. Objectives: To examine whether a novel 'mock medicine' learning activity enabled students to experience the range of barriers and facilitators to medication adherence using the COM-B and TDF. Methods: A mock medicine activity was conducted with students at pharmacy schools in three universities in the UK, Norway, and Australia over one week. Percentage adherence was calculated for five dosing regimens; theoretical framework analysis was applied to map reflective statements from student logs to COM-B and TDF. Results: A total of 349 students (52.6%) returned completed logs, with high overall mean adherence (83.5%, range 0-100%). Analysis of the 277 (79.4%) students who provided reflective statements included barriers and facilitators that mapped onto one (9%), two (29%) or all three (62%) of the COM-B components and all fourteen TDF domains (overall mean = 4.04; Uni 1 = 3.72; Uni 2 = 4.50; Uni 3 = 4.38; range 1-8). Most frequently mapped domains were 'Environmental context and resources' (n = 199; 72%), 'Skills' (n = 186; 67%), 'Memory, attention and decision-making' (184; 66%) and 'Beliefs about capabilities' (n = 175; 63%). Conclusions: This is the first study to utilise both COM-B and TDF to analyse a proxy measure of medication adherence in pharmacy education. Data mapping demonstrated that students experienced similar issues to patients when prescribed a short course of medication. Importantly, all the factors influencing medication-taking reported by students were captured by these two psychological frameworks. Future educational strategies will involve students in the mapping exercise to gain hands-on experience of using these psychological constructs in practice.